Single Linked List Method for Selection of SMA / SMK in Semarang Based on Nearest Neighbor Algorithm and Spatial Buffering Analysis - Alvin Chrismono; Dewi Handayani Untari Ningsih (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2022)
Sistem Zonasi diterapkan sejak adanya Peraturan Menteri Pendidikan dan Kebudayaan Republik Indonesia No. 14 Tahun 2018 Pasal 16 ayat 1 tentang Penerimaan Peserta Didik Baru pada Taman Kanak Kanak, Sekolah Dasar, Sekolah Menengah Pertama, Sekolah Menengah Atas, Sekolah Menengah Kejuruan, atau bentuk lain yang sederajat, menegaskan bahwa sekolah yang berada di bawah naungan pemerintah wajib menerima calon peserta didik yang berdomisili pada radius zona terdekat dari sekolah paling sedikit sebesar 90% dari total jumlah peserta didik yang diterima. Analisa spasial digunakan untuk membuat zonasi kawasan berdasarkan analisa radius dari siswa berada ke beberapa SMA / SMK yang terdekat dengan memanfaatkan metode single link list dan algoritma nearest neighbor. Pemilihan itu pemilihan sma dan smk dalam satu zonasi yang menjadi prioritas adalah berdasarkan titik longitude dan latitude rumah siswa. Perhitungan jarak menggunakan Euclidian distance untuk mengetahui posisi siswa apakah masih di dalam satu zonasi atau tidak dan untuk mengetahui jarak optimal perhitungan rumah siswa ke sekolah. Hasil dari penelitian ini adalah sistem rekomendasi zonasi pemilihan SMA / SMK berdasarkan jarak terdekat dari rumah siswa sebagai pengguna. Kata Kunci: Metode single linked list, Sistem Zonasi, Sistem Rekomendasi, Analisis Spasial buffering, Algoritma Nearest NeighborThe Zoning System has been implemented since the Regulation of the Minister of Education and Culture of the Republic of Indonesia No. 14 of 2018 Article 16 paragraph 1 concerning the Admission of New Students to Kindergarten, Elementary School, Junior High School, Senior High School, Vocational High School, or other equivalent forms, confirms that schools under the auspices of the government must accept candidates students who live in the radius of the nearest zone from the school are at least 90% of the total number of students accepted. Spatial analysis is used to zoning the area based on the radius analysis of students being to several nearby SMA / SMK by utilizing the single link list method and the nearest neighbor algorithm. The selection is the selection of SMA and SMK in one zoning which is a priority based on the longitude and latitude points of the student's house. Calculation of distance using Euclidian distance to determine the position of students whether they are still in one zoning or not and to determine the optimal distance calculation of the student's home to school. The result of this study is a zoning recommendation system for the selection of SMA / SMK based on the closest distance from the student's house as a user.